1961
DOI: 10.1071/ea9610150
|View full text |Cite
|
Sign up to set email alerts
|

Root weight profiles of eight species of Trifolium grown in swards.

Abstract: Weight distribution and depth of the root systems of a number of Trifolium species and varieties were measured at full flowering. In general the root systems increased both in weight and depth with increasingly later flowering, but root depth appeared to be also a specific character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1962
1962
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Subterranean, persian, and berseem clover are often not as drought tolerant as other annual clovers and prefer soils with better water holding capacity (13). Subterranean clover has lower rooting depth than other annual clovers (14), which affects its drought tolerance. Persian, berseem, and balansa clover are better adapted to clay and silt loams rather than sandy loams with lower water holding capacity.…”
Section: Second Year Legume Reseeding Stand Density and Yieldmentioning
confidence: 99%
“…Subterranean, persian, and berseem clover are often not as drought tolerant as other annual clovers and prefer soils with better water holding capacity (13). Subterranean clover has lower rooting depth than other annual clovers (14), which affects its drought tolerance. Persian, berseem, and balansa clover are better adapted to clay and silt loams rather than sandy loams with lower water holding capacity.…”
Section: Second Year Legume Reseeding Stand Density and Yieldmentioning
confidence: 99%
“…Within species, large plants normally have greater root lengths than small plants (Taylor and Klepper, 1978). Large genetic variation for the root weight, root length, root number, root diameter, and rootto-shoot ratios were reported in subterranean clover (Trifolium subterraneum L. ; Humphries and Bailey, 1961), in small grain cereals Blum et al, 1983;Morita et al, 1988). Comparison of two barley genotypes in a field experiment in Syria, demonstrated that the local landrace had a larger root-system at deep depths and was able to extract more water slightly earlier in the growing season (Brown et al, 1987;.…”
Section: Root Developmentmentioning
confidence: 99%